TRANSLATION OF THE FRAGMENTS OF THE POEM BY K. DONELAITIS “GADALAIKI” IN THE CONTEXT OF THE LATVIAN LITERATURE OF THE FIRST HALF OF THE 19TH CENTURY - KLEKERE, INĀRA (Knygotyra, 2015)
The paper is dedicated to the translation of the fragments by K. F. Vatson of “Gadalaiki” (The Seasons) by K. Donelaitis in Latvian, – two opening fragments of the poem in the annual sets of 1822 and 1823 of the calendar of Kurzeme “Veca un jauna laika grāmata” (Book of an Old and a New Time), emphasizing the position of this publication in the context of the Latvian literature of the 20-ies of the 19th century. The Latvian literary theory traditionally interprets the translation by K. F. Watson emphasizing typological literary features of enlightenment that are common to this work. However, by the time when Watson’s translations were published, the ideas of the Enlightenment to a large extent had been already depleted, and in the Latvian literature influences of the early Romanticism were already noticeable. As it happens in other instances when we encounter distinguished examples of the word art, the text in “Gadalaiki” is also characterised by its timeless nature and universalism opened up possibilities to diverse interpretation and stood the test of time. “Gadalaiki” is related to the new values that were brought to the fore at the turn of the 18th and the 19th centuries into German and a little bit later also into Latvian literature by early Romanticism. In the translation of “Pavasara līgsmība” (Rejoicing of Spring) it is testified by the descriptions of revival of the nature and “non-pedagogical” childhood. Statements made against (the source text in Lithuanian; the translation in Latvian) sometimes uncritical attitude of the peasants towards “Germanism” and derogation of one’s own nationality bears resemblance to the attitude held by Johann Gottfried von Herder and later by representatives of the early Romanticism towards national identity as a phenomenon that is worthy of attention and research. It is not known whether Watson knew Lithuanian, however, we have to take into account that the bilingual Lithuanian and German edition was used for translation. Watson distinguished the familiarity of both Baltic languages – Latvian and Lithuanian, and according to him the Latvian language was just a “strongly” modified dialect of the Lithuanian language.